2011
DOI: 10.1016/j.ijbiomac.2011.05.025
|View full text |Cite
|
Sign up to set email alerts
|

A novel globular protein electrospun fiber mat with the addition of polysilsesquioxane

Abstract: The aim of this work has been to elaborate well defined gliadin nanofibers with incorporation of inorganic molecules, such as polyhedral oligomeric silsesquioxane (POSS). Nanofibers were obtained by electrospinning processing, controlling the relevant parameters such as tip-to-collector distance, voltage and feed rate. The fiber mats were characterized by SEM, confocal images, DSC, viscosity, FTIR and conductivimetry analysis. FTIR spectra showed characteristic absorption bands related to the presence of POSS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The application of gliadin microspheres as carriers for drug/nutrient delivery have been explored further (Wan et al, 2015). Although there exist several reports on the electrospinning of gliadin, in which acid or basic solutions have been explored as working fluids with the help of additives, such as polyhedral oligomeric silsesquioxane (Soares et al, 2011;Wang et al, 2012), no report has yet to explore the applications of electrospun gliadin fibers in drug delivery to the best of our knowledge. According to the most recent investigations, these medicated gliadin fibers have the potentials to be developed into commercial tablets or capsules (Démuth et al, 2016;Illangakoon et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The application of gliadin microspheres as carriers for drug/nutrient delivery have been explored further (Wan et al, 2015). Although there exist several reports on the electrospinning of gliadin, in which acid or basic solutions have been explored as working fluids with the help of additives, such as polyhedral oligomeric silsesquioxane (Soares et al, 2011;Wang et al, 2012), no report has yet to explore the applications of electrospun gliadin fibers in drug delivery to the best of our knowledge. According to the most recent investigations, these medicated gliadin fibers have the potentials to be developed into commercial tablets or capsules (Démuth et al, 2016;Illangakoon et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of plant materials such as wheat gluten and gliadin also may enable the cost-effective production of novel electrospun biomaterials [72,73].…”
Section: Electrospinningmentioning
confidence: 99%
“…Wu et al reported on the preparation of nanostructured fibrous hydrogel scaffolds of POSS-poly(ethylene glycol) hybrid thermoplastic polyurethanes incorporating Ag for antimicrobial applications [24]. Soares et al reported a novel globular protein electrospun fiber mat with the addition of POSS, which may extend their use to biotechnology, drug delivery systems, textiles or advanced functional systems [25]. Coleman et al reported the functionalized carbon nanofibers (CNF) with POSS for use as sensors [26].…”
Section: Introductionmentioning
confidence: 99%